Staging (E)motions: The Importance of Elvira Notari’s ‘city films’ for Twentieth-Century Immigrant and Female Audiences (Altre Modernità, 2022)
This article explores the significant social changes registered by woman film director Elvira Notari in her city films, particularly regarding the position of women and Italian immigrant audiences in the US. It thus suggests new readings of Notari’s work through the concepts of urban capabilities and the flâneuse. As most of her original dense archive has been almost lost, only the extant feature film È Piccerella as well as secondary material and scholarship retrieving her work will be used to analyze the contributions of the director to cultural immigration, gender representation and film history.